Крисп - Лангадасская, Литийская и Рентинская митрополия - Алексий (2015)
Экземпляры: аб. (20160914) / Инвентарный номер: 57123 / Цена: / Сис.шифр: 86.372 / Авт.знак: П 68 / ГРНТИ: 21.15.61 / ББК: 86.372я2